"If I Ever Leave, I Have a List of People That Are Going With Me:" Principals' Understandings of and Responses to Place Influences on Teacher Staffing in West Virginia. (April 2023) - McHenry-Sorber, Erin; Campbell, Matthew P.; Sutherland, Daniella Hall
Purpose: Schools across the predominately rural state of West Virginia are experiencing widespread teacher shortages, though recruitment and retention difficulties are unevenly distributed across place. Using spatial in/justice as our framework, we explore how principals define place, how place influences principal perceptions of teacher recruitment and retention, and how principals respond to these staffing challenges given their leadership experiences, relationship to school community, and understandings of place affordances and disadvantages.Research Methods/Approach This research utilized interviews with eight principals across six school districts in West Virginia over a four-month time frame. We inductively coded interview transcripts in iterative cycles using our research framework as a guide for emic and etic codes.Findings: We find principals' understanding of place influences on staffing to be specific to the unique attributes of each community and the placement of their leadership experiences – as community returners, seasoned though not originally from the community, and new-to-place. Their understandings of spatial in/justice as it relates to teacher staffing shape ideas of place affordances and disadvantages and recruitment and retention practices. These findings complexify the teacher staffing picture across geographically diverse rural places and the responses available to leaders given their leadership experience and relationship to place.Implications for Research and Practice The place-specific influences on teacher staffing problematize statewide policy mechanisms for ameliorating teacher shortages. The findings also suggest the need for further in-depth qualitative research within districts and across states, with an emphasis on racially diverse rural places.